(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2018)
The purpose of this article is to examine the representation of Polish rock in Polish cinema and television in the 1960s and the 1970s, in other words (roughly) the first decade of the existence of Polish rock. My argument is that these films minimize their associations with youth, contemporaneity, modernity, rebellion and a western outlook — typical of rock — amplifying connotations which are not seen as central to the genre, such as its closeness to folk music and national culture. In my research I will draw on the history of Polish popular music and Polish cinema in the 1960s and its interface, and the division between pop and rock.